Training of local councillors in Tanzania: learning `good governance' - Taylor, Harry (1999)
This article reports on an attempt by DfID to support wider political reform in Tanzania by supporting a pilot programme of training for locally elected councillors in an urban local authority, Dodoma. As well as hoping to deliver specific skills development for these councillors, it was also intended to influence attitudes in an emergent multiparty democracy and develop a political culture appropriate to liberal democracy rather than one-party rule. The programme was designed locally with the assistance of consultancy support from IDPM, University of Manchester. The design of the programme was derived from an analysis of the changing role of councillors in Tanzania. The evaluation of the programme revealed a positive impact at both the learning and `job impact' levels, although some of the results may have to be treated with caution. The basic curriculum developed in this pilot programme is believed to be appropriate for replication on a national basis, but there remain a number of logistical, financial and political issues that need to be resolved before `upscaling' to a national level can be attempted with confidence. - Reproduced
Keywords: Training - Tanzania; Local government - Tanzania; Local government